Determinasi Kepemimpinan Transformasional, Etos Kerja, Komitmen Organisasional, dan Motivasi Kerja Terhadap Kinerja Guru SMA Negeri di Kota Denpasar - M.D. Risadiana; A.A.G. Agung; I.M. Yudana (Pascasarjana Universitas Pendidikan Ganesha, 2023)
This study aims to 1) determine the magnitude of the determination of transformational leadership on the performance of public high school teachers in Denpasar city, 2) determine the magnitude of the determination of work ethic on the performance of state high school teachers in Denpasar city, 3) determine the magnitude of the determination of organizational commitment on the performance of state high school teachers in the city Denpasar, 4) knowing the magnitude of the determination of work motivation on the performance of public high school teachers in the city of Denpasar, 5) knowing the magnitude of the simultaneous determination of transformational leadership, work ethic, organizational commitment, and work motivation on the performance of teachers of public high schools in the city of Denpasar. This research is an